Identification of Endophytic Bacteria from Water Hyacinth (Eichhornia crassipes) in Lake Tondano as Potential Agents for Lead Bioremediation - Margi Worang; Helen J. Lawalata; Anita Tengker; Verawati Roring; Dany Posumah; Mercy Rampengan (Advances in Tropical Biodiversity and Environmental Sciences, 2026)
Water hyacinth (Eichhornia crassipes) is a herbaceous plant known to accumulate heavy metals from polluted waters. In Lake Tondano, this plant grows abundantly and helps reduce lead (Pb) levels through bioremediation. This study aimed to identify the genera of endophytic bacteria from water hyacinth (E. crassipes) that have potential as bioremediation agents for lead. This study employed an exploratory, descriptive, quantitative laboratory approach. Samples were collected from E. crassipes plants found in Lake Tondano at three different locations. The isolation method used was direct plating. The research stages included bacterial isolation, lead resistance testing at 50 ppm, lead reduction testing at 10, 20, and 30 ppm, lead concentration analysis, and bacterial identification using morphological and biochemical tests. Three isolates (EG.A1.5, EG.A2.4, and EG.D3.4) were found to be resistant and capable of reducing lead levels. The reduction percentages reached 35.9%, 72.2%, and 55.5%, respectively. Based on morphological and biochemical characteristics, the bacterial genera of three isolates were identified as Salmonella, Enterobacter, and Bacillus.